A base substitution in the donor site of intron 12 of KIT gene is responsible for the dominant white coat colour of blue fox (Alopex lagopus). (6th December 2013) - Yan, S. Q.; Hou, J. N.; Bai, C. Y.; Jiang, Y.; Zhang, X. J.; Ren, H. L.; Sun, B. X.; Zhao, Z. H.; Sun, J. H.
Summary The dominant white coat colour of farmed blue fox is inherited as a monogenic autosomal dominant trait and is suggested to be embryonic lethal in the homozygous state. In this study, the transcripts of KIT were identified by RT‐PCR for a dominant white fox and a normal blue fox. Sequence analysis showed that the KIT transcript in normal blue fox contained the full‐length coding sequence of 2919 bp (GenBank Acc. No KF530833), but in the dominant white individual, a truncated isoform lacking the entire exon 12 specifically co‐expressed with the normal transcript. Genomic DNA sequencing revealed that a single nucleotide polymorphism (c.1867+1G>T) in intron 12 appeared only in the dominant white individuals and a 1‐bp ins/del polymorphism in the same intron showed in individuals representing two different coat colours. Genotyping results of the SNP with PCR‐RFLP in 185 individuals showed all 90 normal blue foxes were homozygous for the G allele, and all dominant white individuals were heterozygous. Due to the truncated protein with a deletion of 35 amino acids and an amino acid replacement (p.Pro623Ala) located in the conserved ATP binding domain, we propose that the mutant receptor had absent tyrosine kinase activity. These findings reveal that the base substitution at the first nucleotide of intron 12 of KIT gene, resulting in skipping of exon 12, is a causative mutation responsible for the dominant white phenotype of blue fox.